Politik für den ländlichen Raum 2007+ - Kirschke, Dieter; Häger, Astrid (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
Rural development has become an important policy field in the European Union. The roots for this policy go back to common structural policy in agriculture and to the common structural and regional policy. The new European Agricultural Fund for Rural Development should further strengthen rural development policy in the period 2007–2013. The new perspective is in line with the changing view on the Common Agricultural Policy cutting down sector-specific market and price policy and developing an integrated policy for rural areas. From a scientific point of view the new policy orientation raises several questions. Rural development policy, basically, is a complex policy decision-making problem requiring sound scientific support.